2008
DOI: 10.1111/j.1365-2850.2008.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

People with learning disabilities admitted to an assessment and treatment unit: impact on challenging behaviours and mental health problems

Abstract: This study describes the evaluation of an assessment and treatment unit for people with learning disabilities. Results showed the main reasons for admission for the 48 people admitted to the unit were because of challenging behaviours and mental health problems. Valid and reliable scales were used to measure the behaviours and mental health problems of those admitted across three-time periods: pre-admission, during admission and post-admission. The analysis found significant reductions in challenging behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(61 citation statements)
references
References 23 publications
0
61
0
Order By: Relevance
“…Given that DD is a complex area, it is reasonable to expect nurses to have specialized knowledge and skills (Higgins 2004; Slevin et al . 2008; Vogel 2007; Xenitidis et al .…”
Section: Resultsmentioning
confidence: 99%
“…Given that DD is a complex area, it is reasonable to expect nurses to have specialized knowledge and skills (Higgins 2004; Slevin et al . 2008; Vogel 2007; Xenitidis et al .…”
Section: Resultsmentioning
confidence: 99%
“…These factors range from genetics, behavioural phenotypes, to increased vulnerability to abuse Slevin, et al, 2008). The presence of mental illness symptomatology, often associated with increased need for support exacerbates this risk.…”
Section: Safety/risk Managementmentioning
confidence: 99%
“…Slevin et al, (2008) also identified the role of the nurse in undertaking special observations in order to maintain the safety of an individual and/or others.…”
Section: Safety/risk Managementmentioning
confidence: 99%
See 2 more Smart Citations